2006
DOI: 10.1051/forest:2006068
|View full text |Cite
|
Sign up to set email alerts
|

Differences in morphological and physiological responses to water-logging between two sympatric oak species (Quercus petraea[Matt.] Liebl.,Quercus roburL.)

Abstract: -Pedunculate (Quercus robur L.) and sessile (Q. petraea [Matt.] Liebl.) oaks are known to display different ecological requirements, particularly relative to root hypoxia induced by water-logging. Q. robur is more tolerant to hypoxia than Q. petraea. We designed an experiment aiming at identifying morphological and physiological responses to root hypoxia that might differ between the two species. Potted seedlings were submitted during seven weeks to a water-logging treatment with O 2 concentrations below 3 mg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 63 publications
5
37
1
Order By: Relevance
“…To our knowledge, no study has yet directly tested the effect of hypoxic conditions on E s . The main effect of flooded conditions on plant carbon metabolism is through the deprivation of oxygen to the root system, which usually leads to a decrease in carbon and energy metabolism at the whole plant level and can induce morphological or phenological adaptations (Parelle et al 2006;Parolin 2001). Our results suggest that these same processes influence stem CO 2 efflux.…”
Section: Seasonal Variationssupporting
confidence: 52%
“…To our knowledge, no study has yet directly tested the effect of hypoxic conditions on E s . The main effect of flooded conditions on plant carbon metabolism is through the deprivation of oxygen to the root system, which usually leads to a decrease in carbon and energy metabolism at the whole plant level and can induce morphological or phenological adaptations (Parelle et al 2006;Parolin 2001). Our results suggest that these same processes influence stem CO 2 efflux.…”
Section: Seasonal Variationssupporting
confidence: 52%
“…Taking into account of these new conditions, photoassimilates and cotyledon carbohydrates could be redirected to parts of the Q. robur root system growing at shallow depths that are more likely to stay in or return to normoxia. In older flooded seedlings, the higher capacity of adventitious roots formation in Q. robur than in Q. petraea was also reported Schmull and Thomas 2000;Parelle et al 2006). Thus, this feature favours the establishment of Q. robur seedlings on water-logging stands and begins as early as the first flush of growth.…”
Section: Discussionmentioning
confidence: 53%
“…Further studies have identified physiological and anatomical features that account for the ecological advantage enjoyed by Q. petraea at the expense of Q. robur, especially under drought stress (Epron and Dreyer 1993;Ponton et al 2001;Thomas et al 2002). However, Q. robur seedlings appear to be more tolerant to hypoxic soil conditions than Q. petraea seedlings Wagner and Dreyer 1997;Schmull and Thomas 2000;Parelle et al 2006).…”
Section: Introductionmentioning
confidence: 93%
“…Although, the actual physiological role of lenticels is still unclear, their presence is often linked to waterlogging tolerance in plants. 56 Moreover, the number of hypertrophied lenticels is more under the water surface that supports the argument stating their involvement in maintenance of plant water homeostasis and deviating from the argument that dictates their role as important facilitators of oxygen entry toward the root system. Their potential role in the plant water homeostasis is evident from their active involvement in partially replacing the decaying roots and facilitating water intake for the shoot.…”
Section: Morphological and Anatomical Modificationmentioning
confidence: 64%